What drives money velocity? - Luca Benati (University of Bern, Department of Economics, 2017)
Since World War II, permanent interest rate shocks have driven nearly all of the fluctuations of U.S. M1 velocity, which is cointegrated with the short rate, and most of the long-horizon variation in the velocity of M2-M1. Permanent velocity shocks specific to M2-M1, on the other hand, have played a minor role. Further, counterfactual simulations show that, absent permanent interest rate shocks, M1 velocity would have been broadly flat, and fluctuations in the velocity of M2-M1 would have been more subdued than they have historically been. We show that failure to distinguish between M1 and M2-M1 causes a significant distortion of the inference, erroneously pointing towards a dominant role for M2 velocity shocks.
Keywords: 330; Money demand; structural VARs; unit roots; cointegration; longrun restrictions